Peningkatan Hasil Belajar Volume Bangun Ruang Menggunakan Pendekatan Realistic Mathematics Education di Kelas V Sekolah Dasar - Putri, Ayuni Eka; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research was motivated by the low learning outcomes of class V students at SDN26 Air Tawar Timur, Padang City. This research aims to describe the improvement in student learning outcomes in the material of geometric volumes and cube relationships and cube roots using the Realistic Mathematics Education approach in class V at SDN 26 Air Tawar Timur, Padang City. This research is classroom action research using two types of approaches, namely qualitative and quantitative approaches. The subjects in this research were 26 class V teachers and students. The research was carried out in two cycles, in each cycle there were four stages, namely planning, implementation, observation and reflection. Data collection techniques use observation sheets, tests and non-tests. The results of the research showed that there was an increase in a) RPP cycle I obtained an average percentage of 88.8%, increasing in cycle II to 94.4%, b) teacher activities in cycle I obtained an average percentage of 84.2%, increasing in cycle II to 92.8%, c) student activity obtained an average percentage of 84.2% then increased in cycle II to 92.8%, and d) student learning outcomes in cycle I obtained an average learning outcome of 74,6% (C). Then it increased in cycle II to 88.4% (B).